Not always ‘squame’: The rare entity of follicular dendritic cell sarcoma of the tonsil presenting with cervical nodal metastases - Brugman, Jaanri (SA J Radiol, 2020)
Although squamous cell carcinoma accounts for the overwhelming majority of head and neck malignant neoplasms, extranodal follicular dendritic cell sarcoma (FDCS) of the pharyngeal region can have a similar clinical presentation. The histopathological features of this rare entity have been described and emphasised in the literature. We present the case of a 65-year-old male patient with FDCS of the tonsil to illustrate the radiologic findings of FDCS and also highlight this infrequent but salient differential diagnosis for adult head and neck neoplasia.